DOI: 10.33540/96
|View full text |Cite
|
Sign up to set email alerts
|

Teacher knows best?

Abstract: Intelligence test reports usually mention a 95% confidence interval. Roughly speaking, such a confidence interval acts as a 'margin of error' with respect to the IQ score acquired by the test subject. But the exact meaning of this interval is often misunderstood. In this chapter, we brush up the use and correct interpretation of the confidence interval in intelligence tests. The examples in our exposition are based on the WISC-III NL .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 149 publications
(268 reference statements)
0
5
0
Order By: Relevance
“…Moreover, social networks channel opportunities to White people to attain job security whereas they do not work for non-White people to the same extent (Baalbergen & Jaspers, 2023). Furthermore, when it comes to education, non-White students were less likely to get scientific schooling advice in some Dutch schools, which is key to attain the most prestigious jobs (Lek, 2020). Thus, the inequality created by colonialism in overseas territories arguably also reflects in the Dutch social structure for the advantage of White people.…”
Section: White Identity Strategies and Historical Linking Of Colonialismmentioning
confidence: 99%
“…Moreover, social networks channel opportunities to White people to attain job security whereas they do not work for non-White people to the same extent (Baalbergen & Jaspers, 2023). Furthermore, when it comes to education, non-White students were less likely to get scientific schooling advice in some Dutch schools, which is key to attain the most prestigious jobs (Lek, 2020). Thus, the inequality created by colonialism in overseas territories arguably also reflects in the Dutch social structure for the advantage of White people.…”
Section: White Identity Strategies and Historical Linking Of Colonialismmentioning
confidence: 99%
“…The decision of which track a child will be enrolled in is based on their results in the primary school end test and their teacher's advice. The combination of these two aspects is beneficial overall, as it leads to lower mis-recommendation rates, when compared to only using the PSET [7]. Using a test such as the PSET to estimate children's educational level has advantages, such as providing an objective insight into constructs that might be difficult for teachers to estimate for multiple individual students [7].…”
Section: Transition From Primary To Secondary Educationmentioning
confidence: 99%
“…The combination of these two aspects is beneficial overall, as it leads to lower mis-recommendation rates, when compared to only using the PSET [7]. Using a test such as the PSET to estimate children's educational level has advantages, such as providing an objective insight into constructs that might be difficult for teachers to estimate for multiple individual students [7]. However, educational experts and practitioners often argue against the use of the PSET to advise students on which track they should enroll in.…”
Section: Transition From Primary To Secondary Educationmentioning
confidence: 99%
“…Based on a study of the first student cohort after the policy change, Van Leest et al (2020) found that approximately 16% of the variance in the level of track recommendations was associated with the school level after taking student performance on the monitoring tests into account. Moreover, Lek et al (2020) found that the effects of gender, ethnicity and socio‐economic status differed greatly between schools. Furthermore, they found that the average teacher recommendation is almost one track higher in a class of students with only highly educated parents than in a class of students with only parents with a low educational background.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, students with higher educated parents more often get higher track recommendations than students with a lower socio‐economic status also after controlling for their performance levels on the school leavers test (e.g. Lek et al, 2020; Traag, 2016).…”
Section: Introductionmentioning
confidence: 99%